RANCANG BANGUN ALARM BELL EMERGENCY STOP ESKALATOR BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN DI POLITEKNIK PENERBANGAN MAKASSAR - Ahmad Gaffar; Irfan; Andi Fadhilah Nugrah (Politeknik Penerbangan Surabaya, 2025)
Escalators are a crucial means of vertical transportation in various public facilities, such as airports. As a vocational educational institution, Makassar Aviation Polytechnic faces the challenge of providing adequate practical facilities, particularly for the 5th semester GSE Maintenance and Airport Equipment courses, which include escalators. This research project, a